The Role of Digital Transformation in Enhancing Organizational Performance in Multisectoral Industries - Fithriawan Nugroho; Aditya Ahmad Fauzi; Rahmad Firdaus; Marna Marna (Jurnal Syntax Transformation, 2024)
In the era of Industry 4.0, the adoption of digital technology has become a key factor in enhancing the competitiveness and performance of organizations across various industrial sectors. Organizations that do not adopt digital technology risk falling behind in terms of operational efficiency, productivity, and customer satisfaction. In Indonesia, the implementation of digital technology in the manufacturing, retail, and service sectors still faces several challenges, including infrastructure limitations and insufficient human resource readiness. This study aims to analyze the impact of digital technology implementation on operational performance in three sectors: manufacturing, retail, and services in the Pangkalpinang region. Using a qualitative case study method, data was collected through in-depth interviews with 15 operational managers and IT staff from three companies in these sectors that have implemented digital transformation in the past five years. The findings indicate that the adoption of digital transformation has improved operational efficiency by up to 30%, employee productivity by 18%, and customer satisfaction by 22% in the retail and service sectors. However, in the manufacturing sector, technological infrastructure limitations hindered optimal results. Digital transformation has a positive impact on operational performance and customer satisfaction, especially in the retail and service sectors. However, additional investment in technological infrastructure is needed in the manufacturing sector to achieve maximum results.